En chantier (Itinera, 2018)
This essay aims at reading Walter Benjamin’s Einbahnstrasse taking into account five interrelated aspects: the “crisis of narrativity” and the kinship of Einbahnstrasse with the surrealist texts and the practice of montage; the importance – not only romantic but also intellectual and political – of Asja Lacis, to whom the work is dedicated; the writing of Einbahnstrasse as an attempt to answer, literarily and politically, to another “Strasse”, the one of the despair and of the inflation in Weimar Republic; the form of the Denkbild; the figure of the child that plays with the debris, like in the case of the poet in Baudelaire or the proletarian children’s theater founded by Asja Lacis – the connection between Spiel and Stoff.